Measuring the Stringency of Land-Use Regulation: The Case of China's Building-Height Limits - Jan K. Brueckner; Shihe Fu; Yizhen Gu; Junfu Zhang (Center for Economic Studies and ifo Institute (CESifo), 2016)
This paper develops a new approach for measuring the stringency of a major form of land-use regulation, building-height restrictions, and it applies the method to an extraordinary dataset of land-lease transactions from China. Our theory shows that the elasticity of land price with respect to the oor-area ratio (FAR), an indicator of the allowed building height for the parcel, is a measure of the regulation's stringency (the extent to which FAR is kept below the free-market level). Using a national sample, estimation that allows this elasticity to be city-specific shows substantial variation in the stringency of FAR regulation across Chinese cities, and additional evidence suggests that stringency depends on certain city characteristics in a predictable fashion. Single-city estimation for the large Beijing subsample, where site characteristics can be added to the regression, indicates that the stringency of FAR regulation varies with certain site characteristics, again in a predictable way (being high near the Tiananmen historical sites). Further results using a different dataset show that FAR limits in Beijing are adjusted in reponse to demand forces created by new subway stops.
Keywords: R14; R52; 330; floor-area ratio; density restriction; urban development; China